Distribution Of N-Alkanes In Surface Soils Of Kuantan City, Pahang, Malaysia - Tay, Joo Hui; Yee, Fong See; Han, Wau Leong; Norhayati, Mohd Tahir (2013)
A study has been carried out to determine the distribution of aliphatic hydrocarbons in surface soils of Kuantan City, Pahang, Malaysia. Thirty soil samples (0-15cm depth) were collected from area around Kuantan City covering town center, schools, recreation areas and industrial zones. Hydrocarbons were extracted with dichloromethane using ultrasonic agitation technique and fractioned with silica-alumina column. Characterization of individual hydrocarbon components was carried out using Gas Chromatography – Flame Ionization Detector (GCFID). Total identified resolved aliphatic hydrocarbon (TIRAH) concentrations in soil samples were found ranging from